2017
DOI: 10.18632/oncotarget.19058
|View full text |Cite
|
Sign up to set email alerts
|

Follicular metabolic changes and effects on oocyte quality in polycystic ovary syndrome patients

Abstract: Polycystic ovary syndrome (PCOS) is a common complex and heterogeneous disorder, affecting up to 10% women at reproductive age. It causes three fourth of the ovulatory infertility and PCOS patients often give poor IVF quality. Although some metabolic profiles have been investigated in PCOS patient sera and urine, the follicular fluid, providing fruitful biochemical information about oocyte environment during development has been ignored. In this work, based on NMR metabolomics approach, metabolic profile of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 32 publications
(33 reference statements)
2
40
0
Order By: Relevance
“…Studies have found that the glycolytic activity was increased in developing follicles and as the diameter of the follicle increased, the rate of lactic acid production in the follicular fluid increased significantly [24]. In addition, the lactic acid content in the follicular fluid of PCOS patients was significantly lower than that of normal women [25]. Our study showed that the expression of GLUT1 was significantly increased in the ovary of PCOS rats, and the expression of HK and PFK was significantly decreased, suggesting that the utilization of glucose in PCOS rats was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the glycolytic activity was increased in developing follicles and as the diameter of the follicle increased, the rate of lactic acid production in the follicular fluid increased significantly [24]. In addition, the lactic acid content in the follicular fluid of PCOS patients was significantly lower than that of normal women [25]. Our study showed that the expression of GLUT1 was significantly increased in the ovary of PCOS rats, and the expression of HK and PFK was significantly decreased, suggesting that the utilization of glucose in PCOS rats was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed a few metabolomic studies that analysed FF from women with PCOS and compared them with healthy controls [44][45][46][47][48]. They were performed with the use of different metabolomic techniques.…”
Section: Metabolomic Profile Of Follicular Fluid Samplesmentioning
confidence: 99%
“…Lactate production is associated with the growth and maturation of ovarian follicles 60,75,76 . Irregular lactate production associated with PCOS may induce dyslipidemia, low-grade inflammation, and AA metabolism in follicular fluids 77 . Insulin is hypothesized to stimulate lactate formation by granulosa-lutein cells which are impaired in insulin resistant PCOS patients 78 .…”
Section: Lactatementioning
confidence: 99%